2005
DOI: 10.1073/pnas.0504520102
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hypoxia-inducible factors in hyperoxia through prolyl 4-hydroxylase blockade in cells and explants of primate lung

Abstract: angiogenesis ͉ prematurity ͉ bronchopulmonary dysplasia ͉ alveolization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 49 publications
1
68
0
Order By: Relevance
“…In the current study, we found that incubation of A549 cells in 95% O 2 fails to alter HIF-1α protein expression at 4 hours and beyond, but increases HIF-2α during recovery only. These outcomes are consistent with those recently reported by Asikainen and colleagues, demonstrating that exposure of A549 cells to 24 hours of hyperoxia does not influence VEGF mRNA, HIF-1α, HIF-2α protein, or total cell-associated VEGF protein levels [30]. Augmented HIF-2α protein expression in the absence of changes in VEGF mRNA expression during recovery may indicate that HIF-2α accumulation is exclusively cytoplasmic.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, we found that incubation of A549 cells in 95% O 2 fails to alter HIF-1α protein expression at 4 hours and beyond, but increases HIF-2α during recovery only. These outcomes are consistent with those recently reported by Asikainen and colleagues, demonstrating that exposure of A549 cells to 24 hours of hyperoxia does not influence VEGF mRNA, HIF-1α, HIF-2α protein, or total cell-associated VEGF protein levels [30]. Augmented HIF-2α protein expression in the absence of changes in VEGF mRNA expression during recovery may indicate that HIF-2α accumulation is exclusively cytoplasmic.…”
Section: Discussionsupporting
confidence: 82%
“…Thereby, DMOG resulted in significant reduction of apoptosis in the postischemic myocardium (Natarajan et al, 2009). Moreover, DMOG can exert cell-toxic properties, especially at higher doses (Asikainen et al, 2005). DMOG is a nonselective PHD inhibitor expected to interfere with all 2-OG-dependent oxygenases affecting a number of important cellular processes such as DNA repair, carnitine biosynthesis, and collagen modifications, and most likely many other functions within the cell, including the Krebs cycle, which were not accounted for (Loenarz and Schofield, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The consequential increase in proangiogenic molecules like Epo and VEGF may be a result of systemic synthesis in the liver and kidney, in addition to local production from retinal cells. Critically, the use of small molecules like DMOG enhances the opportunity to regulate therapeutic angiogenesis in the absence of conventional gene therapy (23)(24)(25) or stem cell therapy (26). In fact, the overwhelming induction of Epo protein synthesis by DMOG and the reported effects of Epo on mobilization of erythroid precursor cells (27)(28)(29) suggest that targeting HIF activation by small-molecule inhibition of HIF-␣ subunit degradation could be a novel therapeutic approach for the treatment of ROP and other ischemia-induced proliferative retinopathies.…”
Section: Discussionmentioning
confidence: 99%